The Influence of Spiritual Sense and Emotional Insights on the Learning Achievement of PAI High School Students in Jakarta - Encep Sehabudin (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Education is a process and strategy carried out by humans in order to prepare the next generation to be able to solve various problems of social life. This study aims to determine and analyze the influence of spiritual intelligence and emotional intelligence on PAI learning achievement at Panglima Besar Soedirman Islamic High School. The research method used is a survey method. The research sample was selected using a random sample method, from a population of 190 taken 42% of the total population. It means that the sample size is 80 students. The results of the research can be seen: (1) Spiritual Intelligence has a direct positive effect on PAI Learning Achievement, the path coefficient y1 = 0.391 with tcount = 2,997 and p-value = 0.004/2 = 0.002 <0.05 or H0 is rejected; (2) Emotional Intelligence does not have a direct positive effect on PAI learning achievement, the path coefficient y2 = -0.452 with tcount = -3.466 and p-value = 0.001/2 = 0.0005 <0.05 or H0 is accepted; (3) Spiritual Intelligence has a direct positive effect on Emotional Intelligence, the path coefficient X1 to X2 (P21) = 0.592, with tcount = 6.487 and p-value = 0.000 = 0.000 <0.05 or H0 is rejected.